Fractals in Engineering
DOI: 10.1007/1-84628-048-6_5
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Fractal Force Chains and Their Effect in Granular Materials under Compression

Abstract: Granular materials forming part of civil engineering structures such as rockfill dams and the granular base in pavement systems are subjected to large compressive stresses resulting from gravity and traffic loads respectively. As a result of these compressive stresses, the granular materials break into pieces of different sizes. The size distribution of the broken granular material has been found to be fractal in nature. However, there is no explanation to date about the mechanisms that cause the granular mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
(31 reference statements)
0
20
0
2
Order By: Relevance
“…: [34,38,40]) have also indicated that the predominant effect of particle crushing is to increase the proportion of fine material without significantly changing the size of the largest particles. To date, the mechanisms that cause the granular material to develop a fractal size distribution are not fully explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…: [34,38,40]) have also indicated that the predominant effect of particle crushing is to increase the proportion of fine material without significantly changing the size of the largest particles. To date, the mechanisms that cause the granular material to develop a fractal size distribution are not fully explained.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the larger coordination number for larger particles outweighs the effect of the strength of individual particles reducing with increasing particle size. However, DEM simulations of direct shear tests on mixtures having a limited number of oversized particles carried out by [39] have shown that the smaller particles exert large compressive forces on a small section of the perimeter of the large particles [40] explain the fractal size distribution of the broken grains by the fact that compression of granular materials, simulated by DEM analyses, results in a network of force chains that are fractal in their intensity and distribution. It may be noted, however, that the numerical experiments were conducted on uniform granular materials with permanent grains.…”
Section: Introductionmentioning
confidence: 99%
“…2 para o cálculo de problemas de autovalores: (2) na seguinte forma matricial equivalente: (3) onde M é a matriz de massa e K é conhecida como a matriz de rigidez. Essa equação de autovalores é então resolvida por um algoritmo de Arnoldi até todos autovalores serem encontrados para um determinado intervalo.…”
Section: Método De Elementos Finitos E Análise De Errounclassified
“…O uso da teoria dos fractais abrange aplicações na área de física [2,3], engenharia química [4,5], finanças [6,5], tráfego de internet [7], processamento de imagens [8,9], dinâmica dos fluidos [10,11], ciência ambiental [12,13], análise de superfícies [14] dentre outros. O motivo dessa gama de aplicações da teoria fractal se deve particularmente a sua característica de descrever a auto-similaridade em diferentes escalas que é uma aproximação do que ocorre na natureza [15,16].…”
Section: Introductionunclassified
“…Additionally, the characteristics of the fabrics of contact forces during one-dimensional compression test are beyond the scope of this paper [14,51]. This study mainly aims to identify the features of the contact force distribution in detail using a fractal model, which is developed to analyze the normal contact force, shear contact force and total contact force in the granular packing [52]. This fractal model can also be used to explain the development of the fractal size distribution.…”
Section: Introductionmentioning
confidence: 99%